Metabolic effects of oral vitamin D supplementation as an adjuvant therapy on subjects with type 2 diabetes - Tafseer, Sana; Khan, Irfan Ahmad; Roy, Avijit; Goyal, Pooja; Chhoker, Virender K.; Singh, Abhishek; Sharma, Priyamvada (International Journal of Basic & Clinical Pharmacology, 2019)
Background: It is common for patients with type 2 diabetes mellitus (T2DM) to have vitamin D deficiency. Aim of the study is to determine the metabolic effects of oral vitamin D supplementation in a cohort of T2DM subjects. Methods: Subjects with T2DM were divided into two groups. Group A (Control) included subjects who received the standard treatment (conventional antidiabetic drugs). Group B (Intervention), apart from the standard treatment (conventional antidiabetic drugs), was also supplemented with Vitamin D3. All the patients were followed up at baseline, 6 months, 12 months and 18 months. Results: Vitamin D deficiency was noted down in all the study subjects. Even after 18 months of supplementation, all subjects remained vitamin D deficient. There was a significant improvement in the circulating levels of 25-hydroxyvitamin D. Improvement in the lipid profile of subjects was observed as evidenced by a decrease in total cholesterol (5.0±0.92 mmol/l) as compared to baseline (5.5±1.6 mmol/l). HOMA-IR changed significantly after 18 months of supplementation from baseline (7.0±1.06 vs 10.8±1.96 nmol/l). Conclusions: Supplementation to achieve higher levels of vitamin D remains a promising adjuvant therapy for T2DM patients. Additionally, the intervention brought out a favourable change in HDL/LDL ratio among study subjects.